THE INFLUENCE OF LIVE STREAMING COMMERCE ON PURCHASE INTENTION FOR BEAUTY PRODUCTS IN SHOPEE E-COMMERCE - Rimbun Adillah Herianto rimbun; Refi Rifaldi Windya Giri (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
As technology advances rapidly worldwide, including in Indonesia, the impact on marketing has led individuals and groups to shift their strategies to online marketing via e-commerce. Shopee has become a popular e- commerce platform among Indonesians. In facing the digital era, Shopee has adopted various innovative marketing strategies, including the use of live streaming to enhance consumer engagement and facilitate online transactions through direct interaction with sellers. This study aims to investigate the influence of live streaming commerce on purchase intention for beauty products in Shopee e-commerce, with trust, product fit uncertainty, and product quality uncertainty as mediating variables. The focus is on two signals from live streaming broadcasters to consumers: physical characteristics and value similarity, which can reduce product uncertainty and increase consumer trust. This descriptive (causal) study employs a quantitative research approach, involving Shopee users in Indonesia who watched live streaming of beauty products in the last six months. We collected data from 400 registered respondents through a Google Form survey with predetermined criteria and analyzed it using SEM and Smart PLS. We found that physical and value similarities between consumers and broadcasters significantly influence product quality uncertainty and trust. High trust in the broadcaster reduces product quality uncertainty and increases purchase intention. Product fit uncertainty also has a negative impact on purchase intention. The lower the consumers' uncertainty about product fit and quality, the higher their purchase intention.